2020
DOI: 10.1108/jfmm-08-2019-0181
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable knowledge from consumer perspective addressing microfibre pollution

Abstract: PurposeThis research investigates sustainable knowledge from a consumer perspective, thereby focussing on the issue of microfibre pollution (MFP) within the context of the athleisure wear industry.Design/methodology/approachThis research is exploratory in nature and supports its findings with 15 in-depth semi-structured interviews with consumers who have an invested interest in athleisure wear and have either a fashion or a textile science background.FindingsThe results provide an insight into how different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…In the related literature, a dearth (Yan et al 2020) has been observed to address consumers' knowledge and EC while mapping their garment purchases and consumption. None of the sources recorded the above-stated relationship in the case of denim jeans.…”
Section: Consumer Knowledge and Ecological Concernsmentioning
confidence: 99%
“…In the related literature, a dearth (Yan et al 2020) has been observed to address consumers' knowledge and EC while mapping their garment purchases and consumption. None of the sources recorded the above-stated relationship in the case of denim jeans.…”
Section: Consumer Knowledge and Ecological Concernsmentioning
confidence: 99%
“…The majority of consumers are not conscious of acquiring products containing MP (Henderson and Green, 2020 ; Ojinnaka and Aw, 2020 ). Yan et al ( 2020 ) found that people are unaware of MP due to their invisibility. Moreover, because of their small size, MP are not easily detectable in the environment; thus, they have only relatively recently been considered as an emerging contaminant (Katsnelson, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Activewear clothing is made from a range of different materials often comprising of a mix between synthetic (human made) and organic depending on the support needed, sweat-wicking properties, and breathability (ÖzdIl and Anand, 2014;Josephson, 2015). Research has shown that the synthetic materials within activewear (and other synthetic/mixed material clothing) shed microfibers (a type of microplastic) into the laundry water every time they are washed (O'Loughlin, 2018;Ross, 2019;Herweyers et al, 2020;Yan et al, 2020). Once laundered, the activewear microplastic-water is treated at wastewater treatment plants (WWTP).…”
Section: "I Do the Sniff Test … And Know They Really Need To Be Washed": Laundering Activewearmentioning
confidence: 99%